Private international law in Commonwealth Africa - Oppong, Richard Frimpong, 1978- (2013)
"This book provides a comprehensive and comparative examination of private international law in Commonwealth Africa. It offers an unrivalled breadth of coverage in its examination of the law in Botswana, the Gambia, Ghana, Kenya, Lesotho, Malawi, Namibia, Nigeria, Sierra Leone, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe. The book is clearly and logically structured - it is organised around broad themes or issues, with country reports and accompanied by detailed commentaries. Drawing on nearly 1500 cases decided by courts in these countries and numerous national statutes, this book covers the four cornerstones of private international law: jurisdiction, choice of law, foreign judgements and arbitral awards enforcement, and international civil procedure. The author also provides an extensive bibliography of the literature on African private international law. Scholars and practitioners alike will find Private International Law in Commonwealth Africa invaluable and illuminating"--
Machine generated contents note: Introduction; Part I. Preliminary Matters: 1. Conceptual issues in choice of law; 2. Foreign law; 3. Domicile; Part II. Jurisdiction: 4. Bases of jurisdiction; 5. Forum non conveniens, lis alibi pendens and forum selection; 6. Limitations on jurisdiction; Part III. Obligations: 7. Contract; 8. Torts; 9. Foreign currency obligations; 10. Bills of exchange; Part IV. Family law: 11. Marriage; 12. Matrimonial causes; 13. Children; Part V. Property, succession and administration of estates: 14. Property; 15. Succession; Part VI. Foreign Judgements and Arbitration Awards: 16. Administration of estates; 17. The common law regime for enforcing foreign judgements; 18. The statutory regimes for enforcing foreign judgements; 19. Recognition and enforcement of foreign arbitration awards; Part VII. International Civil Procedure: 20. Remedies in support of or against foreign judicial and arbitral proceedings; 21. International judicial assistance; 22. Security for costs.
Includes bibliographical references (pages 463-477) and index.
Keywords: Conflict of laws -- Africa, English-speaking.